Teacher’s Strategies in Teaching Speaking for Cadets - Khaira Maulidar; Sofyan A. Gani; Iskandar Abdul Samad (Universitas Syiah Kuala, 2019)
This study aims at finding the strategies used in teaching speaking and the problems faced by the teacher during a teaching process at BP2IP Malahayati Aceh. It also investigated the students’ responses toward the teachers’ strategies by involving two English teachers and two classes of 58 students. To gain the needed data, the writers used classroom observation, interview and questionnaire as research instruments. Classroom observation and interview were used to identify the teachers’ challenges and also strategies in teaching speaking, and questionnaire was utilized to collect the data about students’ responses towards the strategies. The results showed that the teachers used five strategies in teaching speaking for cadets in BP2IP Malahayati Aceh, namely: role play, drilling, games, describing picture, and also discussion group. Moreover, three common obstacles were found during teaching process; limited vocabulary, improper pronunciation, and less confident of the students. This study also showed that students’ responses towards the strategies were positive.